2014
DOI: 10.1097/aog.0000000000000339
|View full text |Cite
|
Sign up to set email alerts
|

Successful In Utero Intervention for Bilateral Renal Agenesis

Abstract: Serial amnioinfusion appears to have mitigated the severe pulmonary compromise that has, in the past, led to the death of newborns with bilateral renal agenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 13 publications
0
56
0
Order By: Relevance
“…This case justified a later intervention by Bienstock et al [14] to promote lung growth in CoBRA with amnioinfusions. This and 8 other case reports have documented adequate neonatal lung function when amnioinfusions were given prenatally in the setting of EPRA [12, 14-16]. These outcomes raise the possibility of pulmonary survival for infants with a disease previously thought to be fatal.…”
Section: Epidemiology Of Epramentioning
confidence: 80%
See 2 more Smart Citations
“…This case justified a later intervention by Bienstock et al [14] to promote lung growth in CoBRA with amnioinfusions. This and 8 other case reports have documented adequate neonatal lung function when amnioinfusions were given prenatally in the setting of EPRA [12, 14-16]. These outcomes raise the possibility of pulmonary survival for infants with a disease previously thought to be fatal.…”
Section: Epidemiology Of Epramentioning
confidence: 80%
“…In 1994, a neonate with CoBRA survived early neonatal life after amnioinfusions were administered from 17 to 33 weeks GA, but ultimately succumbed to dialysis complications after 23 days of life [15]. In 2014, Bienstock et al [14] reported the case of CoBRA in a 34-year-old woman treated with weekly serial amnioinfusions beginning at 24 weeks GA. The infant was born at 29 weeks GA with age-appropriate lung function and received a kidney transplant from her father after 3 years on chronic peritoneal dialysis [12].…”
Section: Rationale For Fetal Therapy To Promote Lung Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental evidence is in favour of its use, which also seems to be supported by recent studies, at least in some cases after the premature rupture of membranes [37][38][39]. Systematic studies on fetuses with ROH have not been performed, yet a recent case report indicates a potential benefit even in a fetus with bilateral renal agenesis [40]. However, amnioinfusion is not without risk and may lead to abortion or rupture of membranes [41].…”
Section: Treatment Options (Ante-and Postnatal)mentioning
confidence: 81%
“…Spaggiari et al [11] reported that 30 of 34 cases (88.2 %) with hypoplastic kidneys complicated by oligohydramnios or anhydramnios were associated with poor outcomes. Bienstock et al [12] reported a case of bilateral renal agenesis treated with serial amnioinfusion in which the newborn survived the newborn period and was able to undergo peritoneal dialysis followed by a planned renal transplantation.…”
Section: Discussionmentioning
confidence: 99%